SURGICAL ASPECTS OF STRUMECTOMY FOR TOXIC GOITTER (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The results of surgical treatment of 112 patients with toxic forms of goiter were analyzed. The technical techniques for performing individual stages of strumectomy have been improved, which made it possible to avoid intraoperative complications. A reduction in the time period for performing complex stages was achieved from 15.8±0.9 to 6.7±0.5 minutes (p